PERLINDUNGAN PENGUNGSI DI KAWASAN ASIA TENGGARA: STUDI PERBANDINGAN SEJUMLAH NEGARA ANGGOTA ASEAN - Santa Indah Theresia Pardosi (Sabtida, 2024)
Abstract Legal problems related to refugees in Southeast Asia are influenced by the absence of specific regulations for handling them, both from ASEAN as a regional organization and from the majority of countries that have not ratified the 1951 Refugee Convention and the 1967 Protocol. As a result, legal protection standards are not uniform and are often more influenced by political interests. rather than humanity. This research examines legal regulations in several Southeast Asian countries in dealing with refugees. The research method used is normative legal research, with statutory, conceptual and comparative approaches. The research results emphasize the importance of strengthening regulations in each country in the Southeast Asia region, regardless of whether they are parties to the convention or not. Keywords: Refugees, Southeast Asia, ASEAN, Comparison Abstrak Permasalahan hukum terkait pengungsi di Asia Tenggara dipengaruhi oleh ketiadaan regulasi khusus untuk penanganannya, baik dari ASEAN sebagai organisasi regional maupun dari mayoritas negara yang belum meratifikasi Konvensi Pengungsi 1951 dan Protokol 1967. Akibatnya, standar perlindungan hukum menjadi tidak seragam dan seringkali lebih dipengaruhi oleh kepentingan politik daripada kemanusiaan. Penelitian ini mengkaji regulasi hukum di beberapa negara Asia Tenggara dalam menangani pengungsi. Metode penelitian yang digunakan adalah penelitian hukum normatif, dengan pendekatan perundang-undangan, konseptual, dan perbandingan. Hasil penelitian menekankan pentingnya memperkuat regulasi di masing-masing negara di kawasan Asia Tenggara, terlepas dari apakah mereka merupakan pihak pihak konvensi ataupun tidak. Kata Kunci: Pengungsi, Asia Tenggara, ASEAN, Perbandingan